B4C enhances the supported platinum DER/HER performance. Issue 8 (27th January 2023) - Li, Yanfeng; Zhang, Shijie; Xu, Weiwei; Jiang, Chenghang; Shao, Liangbin; Wang, Shibin; Wang, Jianguo
Abstract : The high energy barrier of D–O bond breakage leads to a slow kinetic reaction rate in the electrocatalytic deuterium evolution reaction (DER). Abstract : The high energy barrier of D–O bond breakage leads to a slow kinetic reaction rate in the electrocatalytic deuterium evolution reaction (DER). Therefore, the platinum–carbon catalyst (Pt/C) shows unsatisfactory performance in the DER. Here, Pt/B4 C catalysts were constructed via the strong metal support interaction (SMSI) between boron carbide (B4 C) and platinum (Pt). The SMSI influenced the electronic structure and dispersion of Pt, resulting in a higher degree of Pt dispersion on B4 C with stronger electronegativity, and Pt/B4 C thus exhibited better DER/HER performance than Pt/C in acidic and basic solutions. The overpotential was only 48 mV (11 mV) and 47 mV (31 mV) when the current density was 10 mA cm −2 in 1 M NaOD (NaOH) and 0.5 M D2 SO4 (H2 SO4 ), respectively. The Pt/B4 C catalyst activity showed no decay after accelerated durability testing (ADT) and 100 hours of i – t stability testing. Density functional theory (DFT) suggests that the electron rearrangement between B4 C and metallic Pt leads to a stronger electronegativity of Pt, whereas the electron-deficient state of Pt can facilitate the dissociation of D2 O/H2 O and the resolution of D2 /H2 . This research provides a useful new guideline and reference for the preparation of high-performance DER/HER catalysts.